Ciência e biotecnologia: a importância do tema na agenda governamental - Almado, Vítor Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The main objective of this work is to analyze the entry of science and biotechnology themes in the governmental agenda, based on the public policies bibliography. The analyzed period starts in the country's re-democratization, in 1986, and ends in 2020. 6022 data obtained from the Federal Constitution of 1988, legislative publications, and Messages to the National Congress were analyzed. Based on these data, the occurrence and permanence of the topic on the agenda were analyzed, in addition to calculating the correlation between the occurrence in the Messages and the legislation. Thus, it was found that there was a low occurrence, correlation, and permanence in the agenda, with specific moments of punctuation, which were still characterized by representing a small part of the attention. Low correspondence was also identified between the different documents analyzed and the predominance of the Executive.

O principal objetivo deste trabalho é analisar a entrada dos temas ciência e biotecnologia na agenda governamental, a partir de um diálogo com a bibliografia de políticas públicas. O período analisado inicia-se na redemocratização do país, em 1986, e chega até 2020. Foram analisados 6022 dados, oriundos da Constituição Federal de 1988, da produção legislativa e das Mensagens ao Congresso Nacional. A partir desses dados, foi feita a análise de ocorrência e permanência do tema na agenda, além do cálculo da correlação entre a ocorrência nas Mensagens e na legislação. Com isso, constatou-se a baixa ocorrência, correlação e permanência na agenda, com momentos específicos de pontuação, mas que ainda foram caracterizados por representarem pequena parte da atenção. Também foi identificada baixa correspondência entre os diferentes documentos analisados e a predominância da atuação do poder Executivo.
Science and biotechnology: the relevance on the government's agenda
Keywords: Ciências sociais; Ciência política; Políticas públicas; Biopolítica; Biotecnologia